The Penitential Psalms and Ash Wednesday Services in the Book of Common Prayer, 1549-1662 - Charles Whitworth (Revue Française de Civilisation Britannique)
This paper traces the presence and the particular uses made of the seven Penitential Psalms in services for Ash Wednesday and related occasions, in successive versions of the Book of Common Prayer, from 1549 to 1662. A brief history of the Seven Psalms and their place in pre-Reformation liturgy, as set down notably in the Use of Sarum (though they were prescribed in ecclesiastical treatises even earlier), precedes a close examination of the evolution of their use in the first four Anglican prayer books, and in the earliest American (Episcopalian) version (1789). It is notable that the seven Psalms were included, in various groupings and at various points within the Ash Wednesday or Lenten Sunday services, throughout the period of the early revisions of the Prayer Book. The striking symmetry of the Latin incipits of the seven Psalms, and their perceived appropriateness for the services of penitence on Ash Wednesday and other services in Lent, continued to command the attention and respect of revisers of the successive versions of the Book of Common Prayer, as it had done for their predecessors since the early Middle Ages.